Improving Regulatory Service Delivery - World Bank (World Bank, Washington, DC, 2018)
Bangladesh has set up an ambitious target of attaining middle-income status by 2021. To achieve this objective, the economy needs to grow at a sustained rate of 7.5-8 percent annually and this would in turn require an increase in private investment to at least 26.6 percent of GDP from 22 percent in 2016-17. Despite the fact that the government has implemented several policy reforms since 2008, investors still face a number of challenges in establishing and operating a business in Bangladesh. This is reflected in the World Bank Group’s Doing Business report, which finds that Bangladesh ranks 177th amongst 190 countries, making it one of the lowest-ranked economies in the South Asia region. Businesses seeking to operate in Bangladesh have to cope with multiple approvals from several institutions and agencies. A potential private investor has to navigate more than 150 government services to obtain the necessary approvals to start and operate a business in Bangladesh. The processes are regulated by over 36 agencies such as the Bangladesh Investment Development Authority (BIDA), Office of the Registrar of Joint Stock Companies and Firms (RJSC) and the Department of Environment (DoE), with little inter-agency coordination. Navigating the uncoordinated, non-transparent and cumbersome workings of the agencies imposes a high cost on domestic and foreign investors. In addition, the uncertainty and unpredictability of service delivery hampers business activities and operational planning. These challenges affect Bangladesh’s competitiveness and reputation as an investment destination.